Recent Study on Endoplasmic Reticulum Stress (ER Stress) and Unfolded Protein Response (UPR) Occur in a Rat Varicocele Testis Model - Hosseini, Mahshid; Shaygannia, Erfaneh; Rahmani, Mohsen; Eskandari, Anahita; Golsefid, Aram Ahmadzadeh; Tavalaee, Marziyeh; Gharagozloo, Parviz; Drevet, Joël R.; Nasr-Esfahani, Mohammad H. (Highlights on Medicine and Medical Research Vol. 9, 2021)
Using a surgically induced varicocele rat model, we show here strong evidence that the misfolded/unfolded protein response that is part of the stress response of the endoplasmic reticulum (ER) is activated in the varicocele testis (VCL), leading to the induction of apoptosis. To support this hypothesis, it is observed that the spliced variant of the X-box protein 1 (XBP1s), resulting from the activation of the inositol-requiring enzyme 1 (IRE1) membrane sensor, is significantly more represented in VCL testicular extracts. The activation of the IRE1/XBP1s pathway is also supported by the observation that the VCL testes show an increase phosphorylation of the c-Jun-kinase (JNK) known to be one intermediate of this pathway and an increased level of caspase-3, the terminal apoptotic effector, partly explaining the apoptotic status of the VCL testis. We show here that the UPR/ER response is most likely activated in the VCL testis as evidenced by the engagement of the IRE1/JNK/XBP1s pathway.